Exploring the effects of self-reflection practice on cognitive emotion regulation and resilience among mothers of premature neonates - Fatemeh Khoshnavay Fomani; Jila Mirlashari; Hamid Sharif Nia; Jamalodin Begjani; Farzaneh Khoshakhlagh; Maryam Shiri; Erfan Teymuri (Tehran University of Medical Sciences, 2022)
Background & Aim: Despite the well-known benefits of practicing self-reflection in educational settings, little is known regarding the effects of applying it in clinical settings. The objective of the current study was to investigate the effects of self-reflective practice on cognitive emotion regulation and resilience of mothers of preterm infants in the NICU. Methods & Materials: A total of 90 mothers whose preterm infants were admitted to NICU enrolled in the current non-randomized clinical trial study by convenience sampling (n=45 in each group). The data of the control group were gathered prior to the intervention group. Pre- and post-test data were gathered using the demographic questionnaire, the Cognitive Emotion Regulation Questionnaire, and the Conner and Davidson Resilience Scale. Self-reflection practice was designed and conducted based on the Gibbs' reflective cycle for the intervention group, which applied a blended model (face-to-face and virtual). Statistical analysis was conducted by SPSS-25 and using the repeated measure ANOVA. Results: Using ANCOVA, the results indicated that the self-reflection practice was effective in improving cognitive emotion regulation (F=66.01, P≤0.001, Eta=0.60) and resilience (F=89.43, P≤0.001, Eta= 0.67) among mothers in the intervention group.  Conclusion: Self-reflection practice was an effective intervention for improving mothers' skills, helping them be more resilient, and assisting them in regulating their emotions. Further studies should support the current study findings in different clinical settings.